Carbohydrate tolerance in the fruit-eating fish Piaractus mesopotamicus (Holmberg, 1887) - Takahashi, Leonardo Susumu [UNESP]; Ha, Natalia [UNESP]; Pereira, Mayara Moura [UNESP]; Biller-Takahashi, Jaqueline Dalbello [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Hindawi, 2018)
Some fish species have a limited ability to metabolize dietary carbohydrates. An important tool for understanding carbohydrate metabolism is the application of the glucose tolerance test, which can be performed orally or intraperitoneally. To evaluate carbohydrate tolerance in the fruit-eating fish pacu, two experiments were performed, one with oral administration by gavage of three carbohydrate types (glucose, fructose and starch, 2.0 g/kg body weight (BW)) and the other with intraperitoneal injection (IP) of glucose (500 mg/kg BW). Oral glucose resulted in an increase in plasma glucose 2 hr later with the peak at 4 hr (8.30 mmol/L), and return to baseline between 6 and 12 hr; starch administration promoted a peak after 4 hr (7.70 mmol/L), returning to the baseline at 6 hr. The administration of fructose promoted a moderate peak after 2 hr (5.71 mmol/L), and return to baseline for the time points that followed. Elevated serum cholesterol levels were observed 2 and 24 hr after administration of glucose and starch. Hepatic glycogen levels increased within 24 hr, regardless of the type of carbohydrate administered. IP glucose load resulted in a peak of plasma glucose 3 hr post injection (6.91 mmol/L), returning to baseline 6 hr later. There was a reduction in the concentration of triglycerides at 24 hr. The results demonstrate that pacu metabolize both oral (glucose or starch) and intraperitoneal (glucose) carbohydrate loads after 6 hr, suggesting good ability to deal with dietary carbohydrates.
Keywords: fish; glucose; hyperglycaemia; metabolism; omnivorous; pacu